USING PICTORIAL CONTEXT IN PRE READING IN READING ACTIVITY TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI AIR SATAN - Syaprizal S. (Jurnal Perspektif Pendidikan, 2016)
The problem of this study was “Is iteffective to improve Student reading achievement byusing Pictorial Context to the Eighth Grade Students of SMP Negeri Air Satan in the academic year of 2013/2014?” Therefore, the objective of this study was to find out whether or not it was it significant effective to use Pictorial Context In Teaching Reading Comprehension to the eighth grade students of SMP NegeriAir Satan in the academic year of 2013/2014.The writer proposed two hypotheses in this research.They werenull hypotheses (Ho) and alternative hypothesis (Ha).The method applied was pre-experimental with one group pre-test post-test design. The population of this study was all of the eighth grade students of SMP Negeri Air Satan in the academic year of 2013/ 2014 which consistedof 147students. The sample was taken through cluster random sampling. The number of the sample was 35 students. The datawere collected through test that a consisting 20 items of multiple choices. The data obtained were analyzed through three techniques: 1) Individual Score, 2) Minimum Mastery Criteria, 3) Matched t-test. The results of this study shows that: (1) The mean students’ score in the pre-test was 62.57,and the mean score of post-test was 69.42, (2) Comparing to the KKM the mean score of pre-test was 62.57 that was still in”failed” qualification and the mean score of post-test was 69.42,that considered in”mastered”qualification. And (3) The result of matched t-test was 2.8152, which was higher than 1.684value of the ttable of 35 with 95% significant level for one tailed-test. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that it was significantly effective to use Pictorial Context In Teaching reading Comprehension to the eighth grade students of SMP NegeriAir Satan in the academic year of 2013/2014.